Oxidation of carcinogenic benzo[a]pyrene by human and rat cytochrome P450 1A1 and its influencing by cytochrome b5 - a comparative study - Indra, Radek; Moserova, Michaela; Sulc, Miroslav; Frei, Eva; Stiborova, Marie (Neuro endocrinology letters, 2013)
OBJECTIVES: Cytochrome P450 (CYP) 1A1 is the most important enzyme in both activation and detoxification of carcinogenic benzo[a]pyrene (BaP), in combination with microsomal epoxide hydrolase (mEH). To evaluate metabolism of BaP in human, identification of a suitable animal model that mimics the metabolic fate of BaP in human is of great importance. The aim of this work was to compare BaP oxidation by human CYP1A1 and CYP1A1 of one animal model, rat. Investigation of the effect of cytochrome b5 on BaP oxidation by CYP1A1 was another target of this study. METHODS: High performance liquid chromatography (HPLC) was employed for separation of BaP metabolites formed by enzymatic systems. Their structures were identified by mass- and NMR-spectrometry. RESULTS: Human hepatic microsomes oxidized BaP to BaP-9,10-dihydrodiol, BaP-4,5-dihydrodiol, BaP-7,8-dihydrodiol, BaP-1,6-dione, BaP-3,6-dione and BaP-3-ol. The same metabolites were generated by rat liver microsomes, but BaP-9-ol and a metabolite Mx, the structure of which has not been identified as yet, were also formed in these microsomes. Human CYP1A1 expressed with NADPH:CYP reductase (POR) in Supersomes™ oxidized BaP to the same metabolites as microsomes, but BaP-4,5-dihydrodiol has not been detected. Rat recombinant CYP1A1 in this SupersomesTM system oxidized BaP to BaP-9,10-dihydrodiol, a metabolite Mx, BaP-4,5-dihydrodiol, BaP-7,8-dihydrodiol, BaP-1,6-dione, BaP-3,6-dione, BaP-9-ol and BaP-3-ol. Addition of cytochrome b5 to rat and human recombinant CYP1A1 systems led to a more than 2-fold increase in BaP oxidation. CONCLUSION: The results show similarities between human and rat CYP1A1 in BaP oxidation and demonstrate rats as a suitable model mimicking BaP oxidation in human.
Keywords: jaterní mikrozomy; Microsomes, Liver; Cytochrome P-450 CYP1A1; Humans; Cytochromes b5; cytochrom P-450 CYP1A1; cytochromy b5; oxidace-redukce; krysa rodu Rattus; lidé; zvířata; Inactivation, Metabolic; Male; Carcinogens; Benzo(a)pyrene; karcinogeny; Oxidation-Reduction; Rats; Animals; metabolická inaktivace; mužské pohlaví; benzopyren